Optimization Of The Government’s Role In Supporting The Socialization Strategy Of Sharia Pawn Products - Karnawijaya, Ning (IKONOMIKA, 2019)
Sharia pawn products (rahn)  are one of the sharia financial services products that are growing over time. However, this development still requires attention in order to achieve financial inclusion and increase market share of sharia pawn products. One of the efforts to realize this goal is the socialization strategy. The success of socialization is not only the responsibility of the Islamic financial services institution, but also the role and support of other stakeholders, especially the government. The government through BI and OJK has a strategic role in helping these efforts. Optimizing the role of the government in supporting the dissemination of sharia mortgage products can be done with strategic steps namely targetting, integrating, understanding, and implementing.Key words : Role of government, Socialization, Sharia pawning